Evaluation of Waste Containment and Collection at Dramaga Campus, IPB University - Joana Febrita; Jihan Nur Azizah; Zainab Ramadhanis; Shofi Latifah Nuha Anfaresi; Handito Rahman; Rasendriya Arkananta Bhanu Loppies; Naila Fauzia Arwen; Indana Atqiya Kamila (Departemen Teknik Sipil dan Lingkungan IPB, 2026)
Effective waste management at university campuses requires systematic evaluation of containment systems and collection operations. This study assessed waste generation, containment conditions, and collection practices at Dramaga Campus, IPB University, Indonesia. Waste sampling was conducted over eight days at 40 collection points across academic, dormitory, general facility, and canteen zones, following SNI 19-3964-1994. Waste at Taman Semangat Integrated Waste Management Facility (TPST) was sampled on two additional days. Total daily waste generation averaged 3.25 tonnes, yielding a per capita generation rate of 0.13 kg/person/day, which is below the global average for higher education institutions (0.19–0.21 kg/person/day). Organic waste dominated all source zones (39–66% by weight), followed by plastic (17–44%) and paper (10–25%). Waste containment relied on two container types—concrete and plastic—classified as communal containers. Evaluation against SNI 19-2454:2002 revealed multiple non-conformities: absence of waste segregation at source, inconsistent container placement, and underutilized containers at peripheral sites. Waste collection follows a Stationary Container System operated by two colour-coded trucks across two daily shifts. The existing fleet of two active trucks requires a total of five trips per day to remove all generated waste, but the current schedule is insufficient to fully serve all sites daily. Recommendations include spatial redistribution of containers, enforcement of source segregation, and expansion of collection capacity.